The prevalence of pterygium and pinguecula in a clinic population - Kamarudin, Siti Nursyahirah; Yusof @ Alias, Firdaus; Samsimon, Nadia Nabila; Othman, Mohd Syafiq Hakimi; Abdullah, Shahirah; Hilmi, Mohd Radzi; Ahmad, Norsham; Md Mustafa, Md Muziman Syah (2020)
Purpose : This study aimed to measure the prevalence of pinguecula and pterygium from patients pool attending the International Islamic University Malaysia Optometry Clinic (IIUM-OC). This study also aimed to study the differences of pterygium and pinguecula between sexes and ocular surface zones, and their relationship to tear break up time (TBUT) and ocular surface zones. The management of pterygium and pinguecula in IIUM-OC is also reviewed. Method : This is a clinical-record-based retrospective study which the data were retrieved from clinic record of patients that attended the IIUM-OC from January 2017 to September 2018. Pterygium and pinguecula cases were identified from the clinic records. Data retreived from the record includes sexes, affected ocular surface zones, TBUT, and the management given to the patients. Results : The total number of clinic records considered in this study were 1229. There were 30 patients diagnosed with pinguecula, and 48 patients with pterygium, giving rise to a prevalence of 2.4% and 3.9%, respectively. There were 21 cases reported in males, for pterygium and pinguecula, respectively. The prevalence of pterygium was significantly higher in female (chi-square test; p=0.02) while the prevalence of of pinguecula was significantly higher in male (chi-square test; p=0.02). The mean age of male patient diagnosed with pterygium was 54.24±11.89 years while female was 48.48±14.57 years. The mean age of male patient diagnosed with pinguecula was 44.24±13.80 years while female was 42.33±14.32 years. There was no association of TBUT with the ocular surface zones in eyes affected with pinguecula and pterygium. The most common management for patient with pinguecula and pterygium was by monitoring through series of follow up. Conclusion : Pterygium and pinguecula is prevalent among patients attended in IIUM-OC. The optometric management of pinguecula and pterygium should be improved for for a better patient care.